Retrospective study of outbreaks of foodborne diseases in the Northeast and State of Maranhão, from 2007 to 2019 (Research, Society and Development, 2021)
The incidence of foodborne diseases grows every year in Brazil, but it is estimated that a high number of cases is not reported. The objective of this work will be to carry out a retrospective study of the occurrence of outbreaks of foodborne diseases in the state of Maranhão, from 2007 to 2019, where a descriptive cross-sectional study was carried out, using as a database the Information on Notifiable Diseases - SINAN. During the study period, 48 outbreaks of foodborne diseases were identified in the state of Maranhão, with 2,535 patients. The etiologic agents identified were Salmonella sp. (6.25%), Escherichia coli (4.17%), rotavirus (4.17%), Staphylococcus aureus and coliforms, both with 2.08%, however, in 81.25% of outbreaks, the etiologic agent is not It was identified. The residence was the place of occurrence with the highest number of outbreaks (37.5%), followed by cases dispersed in the neighborhood (12.5%) and restaurant / bakery (10.42%), it is still important to mention the occurrence of 3 outbreaks (6.25%) in hospitals / health units. As for the origin, in 47.75% of the outbreaks, the food involved in the outbreak was not identified and water and mixed foods were the most common, with a frequency of 14.58% and 12.5%, respectively. As for the confirmation criteria, in 52.08% of the outbreaks the clinical-epidemiological criterion was used, 14.58% performed bromatological analyzes for confirmation and 10.42% only clinical, inconclusive and ignored criteria represented 22.92%. Differences in the number of outbreaks reported during the study period can result from a possible underreporting, causing gaps in the results found.